Impact of low‐frequency noise variability on statistical parameter extraction in ultra‐scaled CMOS devices. Issue 19 (1st September 2014) - Ioannidis, E.G.; Theodorou, C.G.; Haendler, S.; Dimitriadis, C.A.; Ghibaudo, G.
Abstract : The impact on the extracted low‐frequency noise (LFN) parameter values due to LFN variability in CMOS devices is investigated. First, it is demonstrated that the noise level dispersion follows a log normal statistical distribution. Then, based on this feature, it is explained why the mean values from the linear data are different from the mean values (or median values) calculated from the log noise data. Finally, the consequence of this finding in terms of LFN characterisation issues and Monte Carlo LFN variability circuit simulation is discussed.